1999
DOI: 10.7748/ns1999.09.13.52.44.c2678
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of hypodermoclysis

Abstract: Hypodermoclysis (subcutaneous fluid administration) is a valuable means of replacing fluids and maintaining hydration for older people and palliative care patients. This literature review looks at three aspects of the therapy--client groups, wound care and types of infusion fluids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…It was hypothesized that inadequate skin preparation or lack of a standardized protocol for care of the site may have contributed to abscess formation 23 . Although no research related to prevention of site infection for HDC was found in the literature, some advise using the same skin preparation and wound dressing as used for IV 13,24 . Site change is recommended every 24 to 48 hours or after 1.5 to 2 L of infusion 24,25 and change of the administration set every 3 to 5 days 13,24,25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was hypothesized that inadequate skin preparation or lack of a standardized protocol for care of the site may have contributed to abscess formation 23 . Although no research related to prevention of site infection for HDC was found in the literature, some advise using the same skin preparation and wound dressing as used for IV 13,24 . Site change is recommended every 24 to 48 hours or after 1.5 to 2 L of infusion 24,25 and change of the administration set every 3 to 5 days 13,24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…23 Although no research related to prevention of site infection for HDC was found in the literature, some advise using the same skin preparation and wound dressing as used for IV. 13,24 Site change is recommended every 24 to 48 hours or after 1.5 to 2 L of infusion 24,25 and change of the administration set every 3 to 5 days. 13,24,25 It is generally agreed 17 and Dasgupta et al 16 did not report adverse event frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…It is used when patients are having difficulty taking oral fluids, for example, older patients or those with dysphagia. However, this method is not recommended for rehydration in an acute emergency (Donnelly 1999).…”
Section: Subcutaneous Injectionsmentioning
confidence: 99%
“…Resultados que fueron confirmados por un estudio clínico con asignación aleatoria que evaluó la variabilidad del perfil funcional renal en pacientes expuestos a la administración de líquidos por vía intravenosa o subcutánea 5 . A la fecha, la hipodermoclisis ha sido bien caracterizada a través de múltiples reportes en la literatura médica [6][7][8][9][10][11][12][13] . Recientemente, un estudio integrativo validó el uso de 13 medicamentos por VS, revelando que solo la morfina y los cristaloides presentan un buen nivel de evidencia 14 .…”
Section: Introductionunclassified